Association of a functional FAAH polymorphism with methamphetamine-induced symptoms and dependence in a Malaysian population - Sim, M.S.; Hatim, A.; Reynolds, G.P.; Mohamed, Z. (2013)
Aim: FAAH is a membrane enzyme that terminates the activity of a large class of endogenous signaling lipids. Recent studies suggest that the FAAH Pro129Thr polymorphism is a common mutation in the FAAH gene that is significantly associated with drug-addictive traits. This study investigated the association of the Pro129Thr polymorphism of the FAAH gene with methamphetamine dependence, methamphetamine-induced psychosis, manic episodes and panic disorder in a Malaysian population. Materials & methods: This polymorphism was genotyped in 232 male methamphetamine-dependent subjects and in 241 male controls of four different ethnicities: Malay, Chinese, Kadazan-Dusun and Bajau. Intergroup statistical analyses were performed by using the chi(2)-square test and Fisher's exact test, where necessary. In cases of multiple comparisons, the Bonferroni correction was performed. Results: Our results indicated that the FAAH Pro129Thr polymorphism showed a significant association with risk of methamphetamine dependence in the pooled subjects (odds ratio OR: 2.017; p < 0.001) and in the Malay (OR: 2.829; p < 0.001) and Chinese (OR: 3.685; p < 0.001) groups. We also found an association of this polymorphism with episodes of methamphetamine-induced mania in the Malay group (OR: 2.836; p = 0.035). However, there was no association between this polymorphism and age of onset of drug use or the occurrence of methamphetamine-induced psychosis or of panic disorder. Conclusion: Our findings suggest that the FAAH Pro129Thr polymorphism may contribute to methamphetamine dependence in the Malay and Chinese ethnic groups.